Penempatan Pegawai Polis di Sekolah Bagi Mengatasi Masalah Salah Laku Pelajar - Abdul Jalil, Hassan (2001)

(untitled)
Education plays a crucial role in order for Malaysia to achieve the status as a developed country by the year 2020. Besides providing a world class quality education for the nation, the government is also responsible to provide suitable infrastructure and maintain a conducive learning and teaching environment in the schools. Students’ discipline is a major contributing factor to achieve a conducive and suitable atmosphere in the schools. Responsible authorities such as the schools and the Police as law enforcer had taken various means and steps to overcome increasing misconduct among school students. However, the problem has not lessened and has become a national issue. As reports in the media escalate, concern has risen in the community. Parents especially are worried regarding the decline of discipline among the students. The objective of the study is to examine the impact of Police-School Liaison Officer on the misdemeanour and discipline among students. Questionnaires were administered to Principals and Discipline Teachers on the researcher’s visits to 34 secondary public schools in the Kota Setar District. Result of the study shows that the placement of a liaison officer in the school has a positive impact on some misconduct such as criminal offending, sex crimes and vandalism among students. However, it has no effect on misdemeanour, disregard for time and offences during co-curricular activities. On the other hand, programmes organised by the Liaison Officer in the school such as public talk, counselling, check-ups, patrolling the school area and involvement in co-curricular activities helped to curb disciplinary problems among the students.